Revision of Agrilus acutus (Thunberg, 1787) and related species (Coleoptera: Buprestidae) - Jendek, Eduard (Zootaxa, 2004)
A revision of the following species of Agrilus is given: A. acutus (Thunberg, 1787); A. dianthus Kerremans, 1892; A. coelestis Deyrolle, 1864; A. acanthopterus Harold, 1869; A. cyaneofasciatus Th ry, 1930; A. paradiseus Obenberger, 1924 and A. mikusiakorum new species. All species are illustrated. The following taxonomic changes are proposed: A. acanthopterus and A. cyaneofasciatus are revalidated; A. dianthus new status is considered as a species; A. acutus (= frater Deyrolle, 1864 new synonym; = menadoensis Obenberger, 1924 new synonym); A. coelestis (= fructus Kerremans, 1896 new synonym; = lombokanus Kerremans, 1900 new syn- onym; = leniens Obenberger, 1936 new synonym); A. acanthopterus (= luzonicus Kerremans, 1914 new syn- onym; = piperi Fisher, 1921 new synonym); A. cyaneofasciatus (= indius Bellamy, 1998 new synonym). Agrilus mucronatus Boheman, 1858 is a synonym of A. acanthopterus and not A. acutus. Agrilus diacanthus Haan; A. diacanthus Dejean, 1836 and A. asphaltipennis Obenberger, 1924 are unavailable names. Lectotypes of nine species are designated.